2018
DOI: 10.1371/journal.ppat.1006985
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon signaling attenuates regulatory T cell function in viral infection and in the tumor microenvironment

Abstract: Regulatory T cells (Tregs) play a cardinal role in the immune system by suppressing detrimental autoimmune responses, but their role in acute, chronic infectious diseases and tumor microenvironment remains unclear. We recently demonstrated that IFN-α/β receptor (IFNAR) signaling promotes Treg function in autoimmunity. Here we dissected the functional role of IFNAR-signaling in Tregs using Treg-specific IFNAR deficient (IFNARfl/flxFoxp3YFP-Cre) mice in acute LCMV Armstrong, chronic Clone-13 viral infection, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 83 publications
(84 reference statements)
3
79
0
Order By: Relevance
“…Type I IFNs support a vast array of protective host defense mechanisms including the restriction of viral replication 14 , NK cell cytotoxicity 21 , and survival of cytotoxic T cells 22 . In addition, recent studies revealed that type I IFN receptor (IFNAR) engagement also impacts on Treg cell activation and proliferation under inflammatory conditions 23,24 . However, how viral infections and the concomitant type I IFN response might affect the ability of Treg cells to maintain peripheral tolerance has not been addressed.…”
mentioning
confidence: 99%
“…Type I IFNs support a vast array of protective host defense mechanisms including the restriction of viral replication 14 , NK cell cytotoxicity 21 , and survival of cytotoxic T cells 22 . In addition, recent studies revealed that type I IFN receptor (IFNAR) engagement also impacts on Treg cell activation and proliferation under inflammatory conditions 23,24 . However, how viral infections and the concomitant type I IFN response might affect the ability of Treg cells to maintain peripheral tolerance has not been addressed.…”
mentioning
confidence: 99%
“…Comparable differential, seemingly conflicting effects have already been described with regard to regulatory T cells. While type I IFN signaling attenuates Treg function in the tumor microenvironment or during viral infection, IFNAR signaling promotes Treg function in autoimmunity, including EAE [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the Type I interferon signalling pathway plays a predominant role in the immune response to infectious and tumour environments . The immune response is mediated by Type I interferons (IFNs), which are members of the cytokine family including IFN‐α and IFN‐β .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the Type I interferon signalling pathway plays a predominant role in the immune response to infectious and tumour environments. 16 The immune response is mediated by Type I interferons (IFNs), which are members of the cytokine family including IFN-α and IFN-β. 17 IFNs bind to the heterodimeric receptor IFN-α/β receptor (IFNAR), thereby activating Janus kinases (JAK) to induce the phosphorylation of signal transducer and activator of transcription (STAT).…”
Section: Discussionmentioning
confidence: 99%